ANALYSIS OF THE VALUES OF FAITH EDUCATION IN THE BOOK AL-QAULUL JALIYY BY SHEIKH ABDULLAH AL-HARARIY - Rida Haniyah Siregar; Nurmawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This article examines the values of Islamic creed (ʿaqīdah) education contained in the book Al-Qaulul Jaliyy and their relevance to creed education in the modern era. Al-Qaulul Jaliyy is a commentary (sharḥ) written based on the Mukhtashar by Shaykh ʿAbdillāh al-Ḥarariyy and covers major themes including tawḥīd, fiqh, and akhlāq. This study employs a qualitative approach using library research, in which data are obtained through textual analysis of the book and relevant supporting sources. The findings indicate that the values of creed education in Al-Qaulul Jaliyy, particularly the discussion of the meaning of the two testimonies of faith (shahādatayn), riddah (apostasy), and the principles of creed, have strong relevance to Islamic creed education at the level of Islamic educational institutions. These values play an important role in developing a solid understanding of faith and in protecting students from various forms of creed deviation in the modern era.